Influence of Glacial Meltwater on Summer Biogeochemical Cycles in Scoresby Sund, East Greenland - Seifert, Miriam; Hoppema, Mario; Burau, Claudia; Elmer, Cassandra; Friedrichs, Anna; Geuer, Jana K.; John, Uwe; Kanzow, Torsten; Koch, Boris P.; Konrad, Christian; van der Jagt, Helga; Zielinski, Oliver; et al. (Frontiers in Marine Science, 2019)
Greenland fjords receive considerable amounts of glacial meltwater discharge from the Greenland Ice Sheet due to present climate warming. This impacts the hydrography via freshening of the fjord waters and biological processes due to altered nutrient input and the addition of silts. We present the first comprehensive analysis of the summer carbon cycle in the world's largest fjord system situated in southeastern Greenland. During a cruise onboard RV Maria S. Merian in summer 2016, we visited Scoresby Sund and its northernmost branch, Nordvestfjord. In addition to direct measurements of hydrography, biogeochemical parameters and sediment trap fluxes, we derived net community production (NCP) and full water column particulate organic carbon (POC) fluxes, and estimated carbon remineralization from vertical flux attenuation. While the narrow Nordvestfjord is influenced by subglacial and surface meltwater discharge, these meltwater effects on the outer fjord part of Scoresby Sund are weakened due to its enormous width. We found that subglacial and surface meltwater discharge to Nordvestfjord significantly limited NCP to 32 – 36 mmol C m-2 d-1 compared to the outer fjord part of Scoresby Sund (58 – 82 mmol C m-2 d-1) by inhibiting the resupply of nutrients to the surface and by shadowing of silts contained in the meltwater. The POC flux close to the glacier fronts was elevated due to silt-ballasting of settling particles that increases the sinking velocity and thereby reduces the time for remineralization processes within the water column. By contrast, the outer fjord part of Scoresby Sund showed stronger attenuation of particles due to horizontal advection and, hence, more intense remineralization within the water column. Our results imply that glacially influenced parts of Greenland's fjords can be considered as hotspots of carbon export to depth. In a warming climate, this export is likely to be enhanced during glacial melting. Additionally, entrainment of increasingly warmer Atlantic Water might support a higher productivity fjord systems. It therefore seems that future ice-free fjord systems with high input of glacial meltwater may become increasingly important for Arctic carbon sequestration.